2017
DOI: 10.1177/0267659117747693
|View full text |Cite
|
Sign up to set email alerts
|

Is therapeutic hypothermia during neonatal extracorporeal membrane oxygenation associated with intracranial hemorrhage?

Abstract: Therapeutic hypothermia during neonatal ECMO appears to be associated with intracranial hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
7
2
Order By: Relevance
“…Our results indicate a possibility of decreased risk of intracranial hemorrhage and improved survival to discharge with VV ECMO compared to VA ECMO. Some studies in pediatric ECMO population have demonstrated increased risk of mortality and intracranial hemorrhage with VA ECMO compared to VV ECMO [14][15][16]. The loss of pulsatile arterial flow during VA ECMO could disturb cerebral autoregulation and contribute to increased risk of intracranial hemorrhage [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a possibility of decreased risk of intracranial hemorrhage and improved survival to discharge with VV ECMO compared to VA ECMO. Some studies in pediatric ECMO population have demonstrated increased risk of mortality and intracranial hemorrhage with VA ECMO compared to VV ECMO [14][15][16]. The loss of pulsatile arterial flow during VA ECMO could disturb cerebral autoregulation and contribute to increased risk of intracranial hemorrhage [17].…”
Section: Discussionmentioning
confidence: 99%
“…ECMO flow rate and core body temperature were collected daily at 7 AM. Because the use of therapeutic hypothermia was not recorded in the BATE study, therapeutic hypothermia was defined as a core body temperature ≤34°C for two consecutive days during the first three days of ECMO (17). Transfusion volumes included daily volumes of red blood cells, platelets and fresh frozen plasma administered.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective, observational study that included validated data from ELSO registry and did not have neurodevelopmental follow-up data to access long-term efficacy and safety of TH with ECMO (17). On the other hand, a recent study by Cashen et al showed that TH during neonatal ECMO is associated with intracranial hemorrhage, and they suggested to evaluate the patient with considering the potential risks before applying TH with ECMO (20).…”
Section: Discussionmentioning
confidence: 99%